The Application of Blockchain Technology in E-Government in China - Heng Hou (2017 26th International Conference on Computer Communication and Networks (ICCCN), 2017)
The purpose of this article is to discuss the application of blockchain technology in e-government, particularly in the Chinese context. Chancheng District, part of Foshan City in Guangdong Province, China, has undertaken a project called "The Comprehensive Experimental Area of Big Data in Guangdong Province" since 2016. Promoting the application of blockchain technology in e-government is an essential part of this undertaking, which is the first use of blockchain in government in China. Taking Chancheng's project as a case study, this article analyzes the framework, difficulties and challenges of applying blockchain to e-government at present, and discusses how blockchain technology can contribute to the development of e-government and public services in China. This article considers the practical realities in China and discusses the application of blockchain technology in Chinese e-government, finding that blockchain technology can bring the following benefits: (1) improvements in the quality and quantity of government services, (2) greater transparency and accessibility of government information, (3) development of information-sharing across different organizations, and (4) assistance in building an individual credit system in China. However, information security, cost and reliability are still major problems in application. Thus, establishing a general application platform of blockchain technology and developing management standards are crucial for promoting and applying blockchain in e-government. Blockchain provides an effective way of making government services more efficient, but standardizing the management system, processes and responsibility for the application is necessary for its further promotion. This article, by providing an analysis of the practice of blockchain in e-government in China, could serve as a foundation for further practical work and theoretical research in government services.